Flavivirus Receptors: Diversity, Identity, and Cell Entry - Laureti, Mathilde; Narayanan, Divya; Rodriguez-Andres, Julio; Fazakerley, John K.; Kedzierski, Lukasz (Frontiers in Immunology, 2018)
Flaviviruses are emerging and re-emerging arthropod-borne pathogens responsible for significant mortality and morbidity worldwide. The genus comprises more than seventy small, positive-sense, single-stranded RNA viruses, which are responsible for a spectrum of human and animal diseases ranging in symptoms from mild, influenza-like infection to fatal encephalitis and haemorrhagic fever. Despite genomic and structural similarities across the genus, infections by different flaviviruses result in disparate clinical presentations. This review focusses on two haemorrhagic flaviviruses, dengue virus and yellow fever virus, and two neurotropic flaviviruses, Japanese encephalitis virus and Zika virus. We review current knowledge on host-pathogen interactions, virus entry strategies and tropism.